A sensitivity measure of the Pareto set in a vector linfnity-extreme combinatorial problem - V.A. Emelichev; A.M. Leonovich (Computer Science Journal of Moldova, 2001)
We consider a vector minimization problem on system of subsets of finite set with Chebyshev norm in a space of perturbing parameters. The behavior of the Pareto set as a function of parameters of partial criteria of the kind MINMAX of absolute value is investigated.